2010
DOI: 10.1080/07448480903501178
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Web-Based, Tailored, Alcohol Prevention/Intervention Program for College Students: Initial Findings

Abstract: Web-based programs may be useful in reducing alcohol-related risk among college students. Further evaluation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 33 publications
(22 reference statements)
2
53
0
Order By: Relevance
“…Females were more likely to participate in this study (62.1%), however this is similar to other studies [38] and the disparity is not as large as another Australian university study targeting this age group (females 71%) [3]. Selective non-response may have biased these results however levels of alcohol consumption were similar to other studies of this cohort [3] [23] The response rate for this study was low (32.2%) however in their cross sectional study Rickwood and colleagues [3] reported a response rate of 12.9%.…”
Section: Limitationssupporting
confidence: 37%
“…Females were more likely to participate in this study (62.1%), however this is similar to other studies [38] and the disparity is not as large as another Australian university study targeting this age group (females 71%) [3]. Selective non-response may have biased these results however levels of alcohol consumption were similar to other studies of this cohort [3] [23] The response rate for this study was low (32.2%) however in their cross sectional study Rickwood and colleagues [3] reported a response rate of 12.9%.…”
Section: Limitationssupporting
confidence: 37%
“…Of the 100 included studies there were 62 (62%) randomized controlled trials [51ā€“57, 59, 62ā€“73, 75, 77, 78, 82, 84ā€“86, 90, 92, 93, 96, 103, 105, 108, 109, 112, 113, 116, 118ā€“120, 123ā€“125, 127ā€“131, 133ā€“135, 138ā€“140, 143ā€“149], 16 (16%) case series [57, 60, 61, 74, 76, 80, 91, 94, 99ā€“101, 110, 115, 117, 121, 136], 9 (9%) non-randomized controlled trials [87, 95, 98, 102, 104, 107, 122, 137, 141], 7 (7%) cluster randomized controlled trials [79, 81, 83, 111, 126, 132, 142], 4 (4%) cluster controlled studies [45, 88, 97, 114] and 2 (2%) interrupted time series [89, 106]. The number of papers for each study design and reported risk behaviour is provided in TableĀ 3.…”
Section: Resultsmentioning
confidence: 99%
“…Other prevalent settings included military/army (nā€‰=ā€‰11, 11%) [52, 60, 61, 69, 71, 72, 104, 110, 119, 127, 128] and internet (nā€‰=ā€‰8, 8%) [45, 85, 92, 113, 132, 139, 148, 149]. Five studies (5%) were delivered in multiple settings [83, 111, 120, 122, 145].…”
Section: Resultsmentioning
confidence: 99%
“…14 In college populations, tailored interventions delivered via online platforms have been effective at improving health knowledge and behavior in other research areas. 15,16 Because an online intervention could potentially reach many women who otherwise may not receive health messaging related to HPV vaccination, in 2010 our team began developing a novel, online, highly tailored educational intervention for unvaccinated female college students.…”
Section: Introductionmentioning
confidence: 99%